Neurodivergent friendly dbt workbook eaudiobook Coping skills for anger, anxiety, depression, panic, stress. embrace emotional wellbeing to thrive with autism, adhd, dyslexia and other brain differences. - Relief, Instant (VOX PUBLISHING HOUSE LTD, 2022)
Let's face it, the world as it is today wasn't designed for neurodivergent people! This means that as a neurodivergent, you need tools to help you through the tough times as best as possible. One of the best ways to do this is by working within the framework of Dialectical Behavioral Therapy, also known as DBT. DBT skills are very handy and helpful, but here's the rub, it's not often that they're taught in a way that helps people who are neurodivergent. This is why this workbook has been written. Unlike other books out there, you'll find this one very practical , and at no point will you be left scratching your head about what to do or how to be better at dealing with life's stressors. It is written and narrated in simple English , and everything you'll learn is clearly and concisely stated . You'll be able to pick up these skills easily, working at your own pace. Here the most relevant themes covered: What is neurodivergence? A brief overview to help you understand better  Are you neurodivergent? Self-evaluation test, positive sides, and success stories Dialectical Behavioral Therapy: the current gold standard of psychotherapy Strategies for stress, anger, anxiety, panic attacks, depression, and intrusive thoughts Daily plan for emotional well-being This workbook isn't written with the intent to change your personality at its core. It is meant to help you figure out your emotions and regulate them , so they don't overwhelm you to a crippling point. The exercises here will help you learn healthy coping mechanisms for when you're overwhelmed. They'll help you get better at learning what you need, stating those needs clearly, and meeting them yourself when required.  Ready to take control of your life? Grab your copy NOW!